3D kinematic analysis by BodyMech - A Matlab based open source software package for research and education - Harlaar, J.; Doorenbosch, C. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
BodyMech is MATLAB based software designed to be used for human movement analysis in a research laboratory environment. It offers a data-structure that can be used for well designed and maintainable application programs to run for a specific project in a particular laboratory. BodyMech offers also most of the functions that are generally needed for 3D human movement analysis based on marker registration. Finally BodyMech includes a graphical user interface that can be used to interactively analyze and visualize experiments of human movements. BodyMech runs in MATLAB. Users of BodyMech should at least have basic knowledge of structured programming and of the MATLAB programming software.